Persuasion vaccine a factorial quasi-experimental research on the individual and combined effects of inoculation components in building persuasion resistance to anti-free speech persuasion among Filipino high school students - Cruz, Karl Lewis L. (College of Arts and Letters, University of the Philippines Diliman, 2019)
Although the sophistication of modern persuasive transactions deserves to be celebrated. It should be acknowledged that some of these transactions confer harm to the well-being of individuals. Persuading individuals to use illegal drugs, purchase unnecessary products, engage in network marketing scams, demote social equality, and devalue free speech are only some of the transactions recognized as harmful by recent literature. This research focuses on inoculation, a strategy that seeks to protect the belies and attitudes of individuals from the influences of harmful persuasion. The primary objective of the research is to determine the individual and combined effects of inoculation components, threat and refutational preemption, in building persuasion resistance to anti-free speech persuasion. The secondary objective is to formulate an inoculation procedure prototype that can be utilized in both research and practical contexts. This factorial quasi-experimental reseaarch employed one control group and three experimental groups that received different inoculation treatments before being exposed to anti-free speech persuasion. Attitude change levels of individuals from the groups were then measured to determine which treatments resulteed in least attitude change. Various tests of statistical significance showed that full inoculation, treatment involving both threat and refutational preemption, resulted in 76.84% less attitude change. Threat inoculation, treatment involving only threat, resulted in 43.78% less attitude change. Refutational inoculation did not confer a significant level of persuasion resistance. This research also argues that threat component is responsible for the effectiveness of inoculation, making it an indispensable core element of the said strategy. Synthesizing previous literature with the current findings, the researcher also formulated an inoculation procedure prototype that is applicable in research and practical contexts. Decades ago, inoculation introduced itself as a promising resistance strategy. Years later, it continues to exhibit new theoretical and practical dimensions that intrigue researchers and practitioners alike.